Synthesis, structure, and property of a cd(II) 3D coordinated polymer with 2-fold parallel interpenetrated network based on 5-(4-hydroxypyridinium-1-yl) isophthalic acid ligand. Issue 8 (3rd August 2018) - Li, Fu-An; Wang, Li; Yang, Wei-Chun; Li, Qing-Bin
Abstract: A Cd(II) coordination polymer, {[Cd(L)(1, 4-bbi)0.5 (H2 O)]·H2 O} n (1 ), where H2 L = 5-(4-hydroxypyridinium-1-ylmethyl)isophthalic acid, 1, 4-bbi = 1, 1′-(1, 4-butanediyl)bis(imidazole), has been hydrothermally synthesized and structurally characterized by X-ray diffraction analyses and further characterized by infrared spectra (IR), elemental analyses, PXRD, and thermogravimetric (TG) analyses. Compound1 reveals a 2-fold interpenetrating 3D framework with (4·8 2 ·10 3 ) (4·8 2 ) topology, and the Cd center has a distorted octahedral environment. Meanwhile, the luminescent property of the title compound (1 ) has also been investigated in detail.